Conflict Test Battery for Studying the Act of Facing Threats in Pursuit of Rewards - Illescas-Huerta, Elizabeth; Ramirez-Lugo, Leticia; Sierra, Rodrigo O.; Quillfeldt, Jorge A.; Sotres-Bayon, Francisco (Frontiers in Neuroscience, 2021)
Survival depends on the ability of animals to avoid threats and approach rewards. Traditionally, these two opposing motivational systems have been studied separately. In nature, however, they regularly compete for the control of behavior. When threat- and reward-eliciting stimuli (learned or unlearned) occur simultaneously, a motivational conflict emerges that challenges individuals to weigh available options and execute a single behavioral response (avoid or approach). Most previous animal models using approach/avoidance conflicts have often focused on the ability to avoid threats by forgoing or delaying the opportunity to obtain rewards. In contrast, behavioral tasks designed to capitalize on the ability to actively choose to execute approach behaviors despite threats are scarce. Thus, we developed a behavioral test battery composed of three conflict tasks to directly study rats confronting threats to obtain rewards guided by innate and conditioned cues. One conflict task involves crossing a potentially electrified grid to obtain food on the opposite end of a straight alley, the second task is based on the step-down threat avoidance paradigm, and the third one is a modified version of the open field test. We used diazepam to pharmacologically validate conflict behaviors in our tasks. We found that, regardless of whether competing stimuli were conditioned or innate, a low diazepam dose decreased risk assessment and facilitated taking action to obtain rewards in the face of threats during conflict, without affecting choice behavior when there was no conflict involved. Using this pharmacologically validated test battery of ethologically designed innate/learned conflict tasks could help understand the fundamental brain mechanisms underlying the ability to confront threats to achieve goals.